Lead accumulation in plants grown in polluted soils. Screening of native species for phytoremediation - Salazar, María Julieta (2013)
In the present work, we focused on soils contaminated with elevated lead concentrations in an agricultural and residential area surrounding a lead smelter plant in Bouwer, province of Córdoba, Argentina. The aim of this research work was to assess the phytoextraction suitability of native plant species growing in the vicinity of a former lead smelter. The lead concentration in leaves, stems and roots was determined in ten species collected at ten sampling sites along a lead concentration gradient in soil. It was found that at circa 1,600 μg g-1 Pb HCl 0,5 M extractable concentration in soil two native species, Tagetes minuta L. and Bidens pilosa L. accumulated high values of Pb concentration in leaves (380.5 μg g-1 DW and 100.6 μg g-1 DW, respectively). Therefore, Tagetes minuta L. and Bidens pilosa L. have a considerable phytoremediation potential for lead polluted soils. At the same sampling site, Sorghum halepense (L.) Pers., a non-native species, only bioconcentrate lead in roots (1,406.8 μg g-1 DW) showing a phytostabilization potential. The results of this study should be further developed in order to confirm the potential use of these species in soil remediation programs.